2019
DOI: 10.1111/wej.12490
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus retention and loss in three types of soils with implications for geographical pattern of eutrophication in China

Abstract: Phosphorus (P) loss from soil to water bodies is an important process associated with eutrophication of lakes and reservoirs. Phosphorus concentration in China's waterbodies changes geographically, increasing substantially with latitude. It is assumed that the geographical pattern results from change in soil retention and loss features of P. To test this assumption, we designed a soil column leaching experiment to measure the P retention capacity of three common types of soils in China: red, black and loess. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This suggests that soil acidi cation will further promote changes in soil chemical properties in Wuhan city. It has been reported P is generally lacking in the acidic red soil in central and south of China (Ao et al 2014;Huang et al 2019a;Peng et al 2020). Leaves returns part of P to the tree body before falling in P-poor areas (Du et al 2020;Peng et al 2023), therefore, the similar lower values of litter P and soil P con rmed that the P limitation in urban forests where has more acidic soils.…”
Section: ; Du Et Al 2022a)mentioning
confidence: 99%
“…This suggests that soil acidi cation will further promote changes in soil chemical properties in Wuhan city. It has been reported P is generally lacking in the acidic red soil in central and south of China (Ao et al 2014;Huang et al 2019a;Peng et al 2020). Leaves returns part of P to the tree body before falling in P-poor areas (Du et al 2020;Peng et al 2023), therefore, the similar lower values of litter P and soil P con rmed that the P limitation in urban forests where has more acidic soils.…”
Section: ; Du Et Al 2022a)mentioning
confidence: 99%
“…When pH becomes neutral or slightly alkaline, soil particles become negatively charged, and the mineral surface repels negatively charged organic molecules/colloids containing P, limiting the complexation of these P compounds on the soil mineral surface. Peng et al [90] found that acidification tends to promote soil phosphorus loss into water bodies.…”
Section: Influence Of Soil Phmentioning
confidence: 99%
“…The flooding conditions will promote the reloss of P from soil to water. Under hydraulic erosion, soil phosphorus released by hydrolysis enters adjacent water along with surface runoff and soil erosion [90]. Xu et al [94] demonstrated that residual P (H 2 SO 4 -H 2 O 2 digestion) decreased by 18-27% in flooded paddy soil compared with aerobic soil.…”
Section: Influence Of Water Conditionmentioning
confidence: 99%
“…Only K01083 (bpp) was positively correlated with AP and TP in NPKGM. A possible mechanism was the phosphate released from soil minerals being easily leached from red paddy soil under high precipitation (Peng et al, 2020), while the organic phosphorus released from milk vetch rotation could remain longer in soil (Zhao et al, 2013), hence we observed a significant positive correlation between K01083 and soil phosphorus content even when the abundance of K01083 was low (Jorquera et al, 2013). In addition, encoding phytases that catalyze the hydrolysis of plant-sourced phytate (Lu et al, 2022) and taxa containing bpp could benefit in soil with greater plant litter input (Liu X. et al, 2022).…”
Section: Keystone Taxa and Their Predicted Function Promoted Soil Pho...mentioning
confidence: 99%